(3TQM eNJUQ CHj LYaQ GdWMGhis - (3eMeO Hf CMeO GdNLfOi GdESHjLGHis; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3Chd GdcJGH s
(3BNQgG (B:s
(3BNQ cJGH GdLhGdI hGdcaGdI hGdVeGf s
(3GdfSNI HgG MhGTs
(3GdfUa GdChd efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
Keywords: (3Gdabg GdMfajs